A framework for interpreting experimental errors in VISIR - Garcia-Zubia, Javier (2021)
Students usually do errors while performing experiments. In traditional, hands-on labs, instructors are able to help students surpass those errors. In non-traditional labs, like virtual labs or simulations, the support is usually provided by built-in mechanisms that prevent erroneous actions or that provide some sort of online assistance. In remote labs, like the Virtual Instruments Systems in Reality (VISIR) remote lab, the same principle applies. This paper describes the very initial stage of a framework for interpreting experimental errors done in VISIR. It considers the course syllabus of electrical circuits and situates the work done till the moment, in relation to that syllabus. Future work is also addressed.